Assessing the Fiscal Burden of Overweight and Obesity in Japan through Application of a Public Economic Framework - Ataru Igarashi; Cillian Copeland; Nikos Kotsopoulos; Riku Ota; Silvia Capucci; Daisuke Adachi (Journal of Health Economics and Outcomes Research)
**Introduction:** Obesity continues to represent a significant public health concern, with a broad impact from both a health and economic perspective. **Objective:** This analysis assesses the fiscal consequences of overweight and obesity (OAO) in Japan by capturing obesity-attributable lost tax revenue and increased government transfers using a government perspective. **Methods:** The fiscal burden of OAO was estimated using an age-specific prevalence model, which tracked the Japanese population across different body mass index (BMI) categories. The model was populated with fiscal data for Japan, including employment activity and government spending, to calculate tax revenue and transfer costs. A targeted literature review was conducted to identify data estimating the impact of OAO on employment, income, sick leave, retirement, and mortality. These modifiers were applied to Japanese epidemiological and fiscal projections to calculate government tax revenue and spending. The incremental impact of reducing OAO in the general population was subsequently calculated. Results were estimated based on the 2023 Japanese working-age population aged 18 to 70 years. **Results:** The total fiscal burden of OAO in Japan, defined as BMI of at least 25, is estimated at US $13.41 billion (¥1925 billion), representing 0.4% of Japan’s gross domestic product. This consists of a loss of $6.3 billion (¥901 billion) and $1.2 billion (¥179 billion) in direct and indirect tax revenue, respectively, due to lower employment and income combined with higher sick leave. Excess OAO-attributable healthcare costs were $5.4 billion (¥769 billion), while additional pension payment spending of $0.5 billion (¥77 billion) was estimated, due to higher levels of early retirement. **Conclusions:** While the health implications of OAO are well documented, this fiscal analysis demonstrates the significant economic burden of OAO both to the healthcare system and broader government accounts. Policies aimed at reducing population-level obesity have the potential to benefit government accounts through increasing employment and reducing public spending, which can offset the cost of implementing these policies.